Development of carbonisation-activation system for production of biochar and activated carbon from oil palm kernel shell - Zainal, Nahrul Hayawin (2018)
Activated carbon is commonly produced through carbonisation process followed by activation process in two separate reactors. These two-steps or separate processes of carbonisation and activation contribute to energy and time consumption, the cost of materials and apparatus and low yield of activated carbon produced. Therefore, the carbonisation-activation system was designed to enable the activation stage to be continuously conducted after carbonisation without termination of the operation. This process could reduce the production cost, energy and time without compromising on the yield and quality of the activated carbon produced, while at the same time avoiding the involvement of chemical agent in the process. Currently, the industry produce biochar by purchasing it from local or from backyard industry, which is producing it through conventional drum kiln or pit kiln methods, where this conventional heating methods will causes to environmental issue such as gaseous emission and particulate matter emission. Therefore, a study of the production of biochar with high higher heating value (HHV) and low gaseous emission from oil palm kernel shell using a microwave-assisted pre-carbonisation system was conducted. Microwave function is to provide heat to biomass materials that has the ability to reduce the treatment time and energy consumption during the pre-carbonisation process. Biochar with high HHV of 27.63 MJ/kg was obtained, whereby the emissions of the particulate matter <10 μm (PM10) was 35 μg/m3 below the standard limits set by the Malaysian Ambient Air Quality Standards (2014). Therefore, the biochar produced using microwave-assisted pre-carbonisation technology proposed in this study can be used as co-combustion for renewable energy generation. The small-scale carbonisation-activation system using electric vertical reactor was developed to produce activated carbon from oil palm kernel shell as a preliminary study. The process from this preliminary study had resulted a high activated carbon yield of 32%, high fixed carbon content of 88.6% with surface area of 305.67 m2/g. The activated carbon was further tested as bio-adsorbent on the removal of methylene blue. About 99.7% of methylene blue has been adsorbed using minimum dosage of bio-adsorbent 0.6 g/L for 24 hours of treatment time. The results have been correlated in the Freundlich isotherm which was well fitted to the experimental data over the methylene blue experimental concentration range with correlation coefficients of R2=0.992. In order to improve the surface area and yield of oil palm kernel shell activate carbon, a double insulated carbonisation-activation reactor was developed. This reactor was double insulated using low cement castable and covered around the internal space of the reactor with stainless steel plated and fibre glass jacketed heat insulation layer, which allow efficient heat transfer into the bed of material in the reactor. The optimisation carbonisation conditions achieved from carbonisation process using microwave-assisted precarbonisation system was applied to the new development double insulated carbonisation-activation system. The temperature of carbonisation process was 400°C for three hours carbonisation time. The activated carbon produced gave the surface area of 935 ± 36.7 m2/g and 30% yield within only seven hours retention time which is the highest compare to the preliminary systems (small-scale carbonisation-activation system). The concentration of carbon monoxide was 8.98 mg/m3 lower than permitted level set by the Malaysian Ambient Air Quality Standards 2015. The activated carbon produced was then used as a bio-adsorbent to treat palm oil mill effluent (POME) final discharge at various dosages using 40 g/L bio-adsorbent, the total suspended solid (TSS), chemical oxygen demand (COD), colour and biological oxygen demand (BOD) were reduced from 240 mg/L, 604 mg/L, 3170 ADMI unit and 100 mg/L to 18 mg/L, 189 mg/L, 80 ADMI unit and 5.1 mg/L, respectively. The concentrations meet the river water quality standard set by Department of Environment Malaysia (DOE), suitable to be applied for wastewater treatment in the palm oil mill. Therefore, the high quality of activated carbon produced using the carbonisation-activation system developed in this study shown it potential for the various application in the palm oil industry.